Elon musk eaudiobook - Isaacson, Walter (Simon & Schuster Audio, 2023)
The #1 New York Times and global bestseller from Walter Isaacson—the acclaimed author of Steve Jobs , Einstein: His Life and World , Benjamin Franklin , and Leonardo da Vinci— is the astonishingly intimate story of the most fascinating, controversial innovator of modern times. For two years, Isaacson shadowed Elon Musk as he executed his vision for electric vehicles at Tesla, space exploration with SpaceX, the AI revolution, and the takeover of Twitter and its conversion to X. The result is the definitive portrait of the mercurial pioneer that offers clues to his political instincts, future ambitions, and overall worldview. When Elon Musk was a kid in South Africa, he was regularly beaten by bullies. One day a group pushed him down some concrete steps and kicked him until his face was a swollen ball of flesh. He was in the hospital for a week. But the physical scars were minor compared to the emotional ones inflicted by his father, an engineer, rogue, and charismatic fantasist. His father's impact on his psyche would linger. He developed into a tough yet vulnerable man-child, prone to abrupt Jekyll-and-Hyde mood swings, with an exceedingly high tolerance for risk, a craving for drama, an epic sense of mission, and a maniacal intensity that was callous and at times destructive. At the beginning of 2022—after a year marked by SpaceX launching thirty-one rockets into orbit, Tesla selling a million cars, and him becoming the richest man on earth—Musk spoke ruefully about his compulsion to stir up dramas. "I need to shift my mindset away from being in crisis mode, which it has been for about fourteen years now, or arguably most of my life," he said. It was a wistful comment, not a New Year's resolution. Even as he said it, he was secretly buying up shares of Twitter, the world's ultimate playground. Over the years, whenever he was in a dark place, his mind went back to being bullied on the playground. Now he had the chance to own the playground. For two years, Isaacson shadowed Musk, attended his meetings, walked his factories with him, and spent hours interviewing him, his family, friends, coworkers, and adversaries. The result is the revealing inside story, filled with amazing tales of triumphs and turmoil, that addresses the question: are the demons that drive Musk also what it takes to drive innovation and progress?